The Role of Networking Behavior in the Internationalization of Turkish Firms - Bozbeyli, Derin (2019)
This study examines the role of networking behavior in the internationalization of Turkish firms. The goal of this study is to answer the question: What kind of an influence does the networking behavior of Turkish firms have on the uncertain environment, which the firms face during the process of foreign market entry? The data, which is collected from 56 respondents, is analyzed with the first model of the moderator analysis. The findings show no support for the claim that networking increases the performance of the firms through reducing the uncertainty. However the findings supports the claim that the networkingincreases the performance of the firms independently from the uncertainty.